Factors Related to Deaths Due to Suicides in Females Aged 12-24 Years (Medico Legal Update, 2021)
Background: Suicide is a global health problem occurring in all parts of the world. It was the secondleading cause of death among 15-29 year olds in 2016. Hence, an understanding of specific factors relatedto suicide would enable prevention strategies to be more sensitive.Method: A cross sectional study was conducted in Department of Forensic Medicine, Gandhi MedicalCollege, Secunderabad, which included all cases of suicidal deaths in females in the age group of 12-24years in the period of January 2017 to November 2018.Results: Majority cases belonged to the age group of 19-24 years (49%). Many victims were from rural area(60%), belonging to middle socioeconomic status (57%) and unmarried (80%). Majority of the victims weregraduates i.e. 32% and 55% of them were students. The leading motive behind the suicides was emotionaldisturbances (21%). Hanging is the most commonly adopted method to commit suicide i.e. 53% of deaths.Conclusions: Most of the factors related to suicide are preventable. Suicides among the young can beprevented by starting student guidance clinics and should also incorporate woman specific strategies likeproviding education, economic security and empowerment of women.